Small molecule inhibitors of RORγt: Targeting Th17 cells and other applications - Huh, Jun R. (2012)
Nuclear hormone receptors (NHRs) form a family of transcription factors that are composed of modular protein structures with DNA- and ligand-binding domains (DBDs and LBDs). The DBDs confer gene target site specificity, whereas LBDs serve as control switches for NHR function. For many NHRs, both endogenous and synthetic small molecule ligands bind to small pockets within the LBDs, resulting in conformational changes that regulate transcriptional activity. This property of NHRs has been exploited by the pharmaceutical industry for therapeutic targeting of a wide variety of diseases, ranging from inflammatory diseases and cancer to endocrine and metabolic diseases. Th17 cells are CD4(+) T helper effector cells that express several pro-inflammatory cytokines, including interleukin-17A (IL-17), and the actions of these cells have been linked to multiple human autoimmune diseases. Our laboratory previously identified the NHR RORγt, an immune cell-specific isoform of RORγ (retinoic acid receptor-related orphan nuclear receptor gamma), as a key transcription factor for the development of Th17 cells both in human and mouse. Although endogenous ligands for RORγt have not yet been reported, it is thought that RORγt activity and Th17-cell development can be modulated with highly specific small molecules that bind to the RORγt LBD and displace its endogenous ligands. Recent studies from multiple groups have reported the activities of such inhibitors. In this mini review, we describe how RORγt inhibitors were identified and how they may contribute to our understanding about RORγt and its biology.